The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2967/jnumed.120.252114
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Biodistribution, and Radiation Dosimetry of 18F-rhPSMA-7.3 in Healthy Adult Volunteers

Abstract: This first-inhuman study investigated the safety, biodistribution and radiation dosimetry of the novel 18 F-labeled radiohybrid prostate-specific membrane antigen (rhPSMA) positron emission tomography (PET) imaging agent, 18 F-rhPSMA-7.3. Methods: Six healthy volunteer subjects (3 males, 3 females) underwent multiple whole-body PET acquisitions at scheduled time points up to 248 minutes after the administration of 18 F-rhPSMA-7.3 (mean activity 220; range, 210-228 MBq). PET scans were conducted in three separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…To translate these animal data into clinical context, two different methodologies for detection of imaging-derived biodistribution of 18 F-rhPSMA-7.3 were applied. Recently, biodistribution of 18 F-rhPSMA-7.3 has been investigated in 6 healthy subjects, where 18 F-rhPSMA-7.3 showed high physiologic uptake in the kidneys and salivary glands (10). Our study demonstrated, that the uptake of most organs is not influenced by receiving lower specific activities as it might occur during clinical practice in a busy PET clinic.…”
Section: Discussionmentioning
confidence: 56%
“…To translate these animal data into clinical context, two different methodologies for detection of imaging-derived biodistribution of 18 F-rhPSMA-7.3 were applied. Recently, biodistribution of 18 F-rhPSMA-7.3 has been investigated in 6 healthy subjects, where 18 F-rhPSMA-7.3 showed high physiologic uptake in the kidneys and salivary glands (10). Our study demonstrated, that the uptake of most organs is not influenced by receiving lower specific activities as it might occur during clinical practice in a busy PET clinic.…”
Section: Discussionmentioning
confidence: 56%
“…The resulting lead candidate [ 18 F]Ga-rh-PSMA-7.3 showed the highest tumor accumulation and low uptake in non-target tissues. This was confirmed in healthy volunteers determining biodistribution and radiation dosimetry data (NCT03995888) and in a larger cohort of patients [ 84 , 195 , 196 , 197 ]. The molar activity of [ 18 F]Ga-rh-PSMA-7.3 had a minor influence on the biodistribution [ 198 , 199 ].…”
Section: Future Methods and Concepts For Psma Inhibitor Radiolabelingmentioning
confidence: 54%
“…In the efficacy cohort, LN metastases were present in 48/420 (11%) resected templates, in 33/166 (20%) hemi-pelvic templates and in 24/83 patients (29%). A total of 1763 nodes were removed with a median (IQR) of 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) per patient. A patient example is presented in Figure 3.…”
Section: Diagnostic Accuracy Of 18 F-rhpsma-73 Pet and Morphological ...mentioning
confidence: 99%
“…To date, the safety and biodistribution of 18 F-rhPSMA-7.3 have been established in healthy volunteers and PCa patients. 18 F-rhPSMA-7.3 has been shown to have low average urinary excretion and diagnostic efficacy has been demonstrated in patients with BCR of PCa (16)(17)(18). 18 F-rhPSMA-7.3 is currently under evaluation in two phase III studies, for primary and BCR PCa (NCT04186845 and NCT04186819).…”
Section: Introductionmentioning
confidence: 99%